Discussion: Should Large Banks be Allowed to Fail? - Hayes, David G. (Journal of Financial and Quantitative Analysis, 1975)
If I have read Professor Mayer's paper correctly, its basic message is that large banks should be permitted to fail. I agree with that position. Moreover, there have been two large-bank failures of late, and it is safe to infer that at least in a technical sense, the regulatory authorities also agree with Professor Mayer's position. However, implementation of that basic policy raises questions about the continued use of what have proved to be important institutional arrangements. As is well-recognized, failure carries with it a host of socially undesirable consequences, and for that reason an elaborate system of bank examination has been created at both the state and federal level to minimize the frequency of its occurrence. Thus, a policy position which permits any bank, large or small, to fail could imply the abandonment of bank supervision. I for one am not willing to go that far and I do not believe Mayer is either.